Automation and the Future of Work (excerpt) - Benanav, Aaron; Protsenko, Nikolai (Journal of Economic Sociology, 2022)
Thinking over what people will do in the automized future, researchers come to the conclusion: we will meet mass technologically-based unemployment, and we will be able to cope with it only by accepting universal basic income as major social groups will lose an opportunity to earn enough money for living. In this book the author critiques the new automation discourse, rejecting the hypothesis that overwhelming technological changes result in destroying jobs. In reality, changes in labor productivity are slowing not speeding up. Coupling with the decline in economic growth, the creation of new jobs is also down. Namely, this fact, and not technological innovations, is responsible for squeezing the demand for labor. In this book, the author opposes the new wave of automation discourse, and suggests his version of history of the global economy and labor development in the last 50 years. The author further believes that the majority of employed people will stop being tolerant of the chronicle decline in demand for labor and resulting economic inequality, which will turn the world towards a more humanized future. The Journal of Economic Sociology publishes the first chapter “Discourse of Automation” in which the author systematizes arguments of the new automation discourse in order to provide his explanations for the declining demand for labor in the next chapters.